Differential effect of plant lectins on mast cells of different origins - Lopes, F.C. [UNESP]; Cavada, B.S.; Pinto, V.P.T.; Sampaio, A.H.; Gomes, J.C. [UNESP] (Associação Brasileira de Divulgação Científica (ABRADIC), 2005)
Histamine release induced by plant lectins was studied with emphasis on the carbohydrate specificity, external calcium requirement, metal binding sites, and mast cell heterogeneity and on the importance of antibodies bound to the mast cell membrane to the lectin effect. Peritoneal mast cells were obtained by direct lavage of the rat peritoneal cavity and guinea pig intestine and hamster cheek pouch mast cells were obtained by dispersion with collagenase type IA. Histamine release was induced with concanavalin A (Con A), lectins from Canavalia brasiliensis, mannose-specific Cymbosema roseum, Maackia amurensis, Parkia platycephala, Triticum vulgaris (WGA), and demetallized Con A and C. brasiliensis, using 1-300 µg/ml lectin concentrations applied to Wistar rat peritoneal mast cells, peaking on 26.9, 21.0, 29.1, 24.9, 17.2, 10.7, 19.9, and 41.5%, respectively. This effect was inhibited in the absence of extracellular calcium. The lectins were also active on hamster cheek pouch mast cells (except demetallized Con A) and on Rowett nude rat (animal free of immunoglobulins) peritoneal mast cells (except for mannose-specific C. roseum, P. platycephala and WGA). No effect was observed in guinea pig intestine mast cells. Glucose-saturated Con A and C. brasiliensis also released histamine from Wistar rat peritoneal mast cells. These results suggest that histamine release induced by lectins is influenced by the heterogeneity of mast cells and depends on extracellular calcium. The results also suggest that this histamine release might occur by alternative mechanisms, because the usual mechanism of lectins is related to their binding properties to metals from which depend the binding to sugars, which would be their sites to bind to immunoglobulins. In the present study, we show that the histamine release by lectins was also induced by demetallized lectins and by sugar-saturated lectins (which would avoid their binding to other sugars). Additionally, the lectins also released histamine from Rowett nude mast cells that are free of immunoglobulins.
Keywords: Mast cells; Histamine; Plant lectins